Alkyl chain engineering of pyrene-fused perylene diimides: impact on transport ability and microfiber self-assembly. (29th August 2017) - Zhan, Xuejun; Zhang, Ji; Gong, Yanbin; Tang, Sheng; Tu, Jin; Xie, Yujun; Peng, Qian; Yu, Gui; Li, Zhen
Abstract : Through alkyl chain engineering, the transport performance of pyrene-fused perylene diimides was systematically investigated. Abstract : The development of new solution-processable organic π systems is significant for the development of organic electronics, especially those with high hole/electron mobilities. Conjugated bilaterally pyrene-fused perylene tetracarboxdiimide (DPPDI) is a new class of material with high mobility and large on/off ratio. In this work, in several pyrene-fused PDIs, the impact of the alkyl chain on the performance has been systematically investigated, including the alkyl type (linear/branch), the alkyl chain length, and the position of the branching point. For the first time, the "antenna effect" has been observed in small molecules. Interestingly, the synthesized DPPDIs can form microfibers, indicating their tendency to form well-organized self-assembled structures. Moreover, a pyrene-fused PDI bearing a 5-decylpentadecyl N -alkyl chain group demonstrates an improved mobility of up to 1.38 cm 2 V −1 s −1, which is the highest hole mobility value among pyrene derivative-based FETs through solution processing.